2010
DOI: 10.1097/imi.0b013e3181cf8228
|View full text |Cite
|
Sign up to set email alerts
|

Off-pump Coronary Bypass Surgery in Patients with Low Ejection Fraction

Abstract: Objective Long-term survival after off-pump surgery in patients with low ejection fraction was investigated. Methods Three hundred forty-six patients with ejection fraction 30% or less with isolated off-pump coronary artery bypass surgery (OPCAB) were compared with a propensity matched historical group operated on-pump (ONCAB) and with data from literature after percutaneous coronary intervention and OPCAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 68 publications
1
8
0
Order By: Relevance
“…However, these are often very ill patients with multiple comorbidities, and their risk of death from a variety of other causes remains high. Similar to the findings of the aforementioned study based on the Society of Thoracic Surgeons database, 5 a large propensity-match study by Gorki and colleagues 18 on 346 patients showed that the OPCAB group had a 30-day survival benefit, shorter postoperative hospital stay, but no difference in postoperative complications. There was no observed long-term survival difference between on- and off-pump CABG.…”
Section: Discussionsupporting
confidence: 72%
“…However, these are often very ill patients with multiple comorbidities, and their risk of death from a variety of other causes remains high. Similar to the findings of the aforementioned study based on the Society of Thoracic Surgeons database, 5 a large propensity-match study by Gorki and colleagues 18 on 346 patients showed that the OPCAB group had a 30-day survival benefit, shorter postoperative hospital stay, but no difference in postoperative complications. There was no observed long-term survival difference between on- and off-pump CABG.…”
Section: Discussionsupporting
confidence: 72%
“…It has been previously shown that in patients with low LVEF who undergo off-pump coronary revascularization via sternotomy, complete revascularization relates to improved survival. 14 We have previously shown that the use of robotic TECAB as part of a hybrid strategy can be effective in achieving complete or near complete revascularization based on residual SYNTAX scores (mean baseline and residual SYNTAX scores 33.1 ± 11.0 and 4.6 ± 6.5, respectively). 15 We believe that this contributes to the outcomes in this cohort as our cardiac-related mortality at a mean follow-up of 37 ± 23 months was only 5%.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, inhospital mortality rates for patients who underwent unplanned conversions were high (12.5% and 9.3%, respectively). A study that propensity matched 346 low LVEF OPCAB patients with a historical cohort of ONCAB patients, noted similar survival at 8 years and suggested that OPCAB may be a viable alternative to improve early outcomes but did not appear to have a survival advantage 10 . Additionally, another unmatched retrospective analysis of patients with left ventricular dysfunction from the late 1990s and early 2000s found similar rates of 10‐year survival between OPCAB and ONCAB patients 15 .…”
Section: Discussionmentioning
confidence: 99%
“…While numerous randomized control trials (RCTs) and meta‐analyses evaluating the potential benefits of OPCAB in the general population have been conducted, the indications for OPCAB and its effect on clinical outcomes remain controversial 2‐6 . Notably, several observational studies that have evaluated high‐risk subpopulations such as patients with reduced LVEF, who are typically excluded from inclusion in RCTs, have shown OPCAB to reduce early morbidity and mortality 7,8,10 . Currently, the longitudinal impacts of OPCAB remain unclear due to the fact that the majority of studies investigating OPCAB in reduced LVEF patients are constrained to immediate postoperative assessments, include patients from prior eras, or have longitudinally followed groups of OPCAB and ONCAB patients, with unbalanced degrees of complete revascularization.…”
Section: Discussionmentioning
confidence: 99%